The Role of Islamic Religious Education Teachers in Improving the Academic Achievement of 8B Grade Female Students at SMP Roudhlatul Quran 3 Sekampung - Fajar Hari Nugroho; Rina Mida Hayati; M. Sayyidul Abrori (Journal of Research in Islamic Education, 2025)
This study aims to analyze the role of Islamic Education (PAI) teachers in improving the academic achievement of 8B grade female students at SMP Roudhlatul Quran 3 Sekampung. Motivated by a decline in student performance evident in the deterioration of learning quality and report card scores this research employs a descriptive qualitative approach involving PAI teachers, the Vice Principal for Curriculum, and 8B grade female students as subjects. Data were collected through observation, interviews, and documentation, and validated using source and technique triangulation. The findings indicate that PAI teachers play a crucial role in enhancing students' academic achievement through several strategies. First, PAI teachers provide concrete examples of the Prophet Muhammad’s (SAW) behavior in daily life, both inside and outside the classroom. Second, they integrate Islamic values such as honesty, discipline, and responsibility into the learning process. Third, PAI teachers offer motivation and guidance to boost students' enthusiasm for learning and to help them overcome academic challenges. Fourth, they employ varied instructional methods, including discussions, lectures, and group assignments, aligned with the assessment instruments of the Kurikulum Merdeka. Fifth, PAI teachers conduct authentic assessments covering aspects of attitude, knowledge, and skills, in accordance with the principles of the Kurikulum Merdeka. The study concludes that the modeling of the Prophet Muhammad’s (SAW) character by PAI teachers positively impacts students’ academic achievement. It is recommended that PAI teachers continue to enhance their competencies in implementing Islamic values within the learning process.